Profil Kemampuan Pemecahan Masalah Soal HOTS Matematika Siswa SMP ditinjau dari Kemampuan Awal - Asdar Asdar; Alimuddin Alimuddin; Sukmawati Ali (Issues in Mathematics Education (IMED), 2022)
Penelitian ini menyajikan profil kemampuan pemecahan masalah matematika level HOTS ditinjau dari kemampuan awal. Jenis penelitian ini adalah penelitian deskriptif kualitatif. Penelitian ini dilakukan di salah satu SMP di Kabupaten Wakatobi. Teknik pengumpulan data yang digunakan yaitu tes tertulis dan pedoman wawancara. Instrumen yang digunakan berupa tes kemampuan awal matematika, tes HOTS matematika, dan pedoman wawancara. Partisipan dalam penelitian ini sebanyak 3 orang siswa dengan kategori kemampuan awal tinggi, kemampuan awal sedang, kemampuan awal rendah. Hasil penelitian menunjukkan bahwa karakteristik siswa tinggi tidak memenuhi semua tahapan pemecahan masalah. Siswa sedang memenuhi semua tahapan pemecahan masalah tetapi masih keliru dalam menuliskan jawaban terkait masalah konteks. Siswa rendah tidak memenuhi semua tahapan pemecahan masalah Polya.Kata kunci: HOTS, Kemampuan Awal, Pemecahan Masalah, Matematika.This study is presents to HOTS level problem solving ability profile in terms of initial ability. The type of research is descriptive qualitative research. This research was conducted in one of the junior high schools in Wakatobi Regency. The data collection techniques in by doing are written tests and interview guidelines. The instruments used are early mathematics ability tests, HOTS mathematics tests, and interviews. Participants in this study were 3 students with high initial ability, moderate initialability, low initial ability. The results showed characteristics of high students does not solve all problem solving. The medium student mastering all problem solving but are still wrong in writing answers related of problems the context. The Low sudent does not meet all of Polya problem solvingKey Words: HOTS, Initial Ability, Problem Solving, MathematicsThis study is presents to HOTS level problem solving ability profile in terms of initial ability. The type of research is descriptive qualitative research. This research was conducted in one of the junior high schools in Wakatobi Regency. The data collection techniques in by doing are written tests and interview guidelines. The instruments used are early mathematics ability tests, HOTS mathematics tests, and interviews. Participants in this study were 3 students with high initial ability, moderate initialability, low initial ability. The results showed characteristics of high students does not solve all problem solving. The medium student mastering all problem solving but are still wrong in writing answers related of problems the context. The Low sudent does not meet all of Polya problem solving. Key Words: HOTS, Initial Ability, Problem Solving, Mathematics